Neuro-oncologists have spoken – the role of bevacizumab in the inpatient setting. A clinical and economic conundrum. Issue 1 (19th April 2018) - Sharma, Akanksha; Low, Justin; Mrugala, Maciej M
Abstract: Background: Bevacizumab is a monoclonal antibody targeting vascular endothelial growth factor (VEGF), a key player in tumor angiogenesis. The drug can halt tumor progression, treat radiation necrosis, and reduce peritumoral edema. Although it does not increase overall survival, bevacizumab can improve progression-free survival and quality of life. In many countries, bevacizumab use in the inpatient setting is restricted due to its significant cost. Here, we explore attitudes towards the use of bevacizumab amidst practitioners treating brain tumors and assess ease of accessing the drug in the inpatient setting. Design/Methods: A 10-question survey querying practitioners' opinions of inpatient bevacizumab utility and its availability was distributed to the membership of the Society of Neuro-Oncology in July 2016. Results: Eighty-seven percent felt that there was a role for bevacizumab in the inpatient setting, and 69% reported favorable experiences with bevacizumab use. However, 40% encountered difficulty in obtaining approval for inpatient use. We present two contrasting clinical cases that highlight favorable and unfavorable outcomes when bevacizumab use was and was not permitted, respectively. Conclusions: In this sample of neuro-oncology practitioners, there is general consensus that bevacizumab plays an important role in the inpatient treatment of brain tumors. In light of ongoing barriers to inpatient bevacizumab use due to cost concerns, these data motivate the creation of standardized policies for inpatient bevacizumab use that balances its important role in improving quality of life with financial considerations.